7(y+3)=2y+77

Simple and best practice solution for 7(y+3)=2y+77 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(y+3)=2y+77 equation:


7(y+3)=2y+77

We simplify the equation to the form, which is simple to understand
7(y+3)=2y+77

Reorder the terms in parentheses
+(+7y+21)=2y+77

Remove unnecessary parentheses
+7y+21=+2y+77

We move all terms containing y to the left and all other terms to the right.
+7y-2y=+77-21

We simplify left and right side of the equation.
+5y=+56

We divide both sides of the equation by 5 to get y.
y=11.2

See similar equations:

| 2c+5=2c+8 | | 3.5n+6.4=42 | | 3x^2=4(3x-8) | | 4x-4x=16+36 | | 2q+12=4k+14 | | (2x+4)(x-3)= | | 34=W/4+20 | | 5y-18= | | X^2+4x+4=24 | | 2X-1=7x+55 | | 24-(8-10x)=4(2x-8)-10 | | 3x+2-5x-7x+9=8x-1+7x | | (9a^6b^4)^91/2) | | y=2(3x+9) | | 2/7*x/y=1/2 | | 1.8y+3=-6 | | 2(N-3)=26 | | 8x+3=17-6x | | 12+6y=8x | | 4x+4-5x=43 | | 15n-13n-2n+3n-2n=16 | | 28+4m=6(m-8) | | 3.6+b=53.2 | | -5-8p=2(8-4p) | | 7f-3f-f=15 | | 5n=4m-120 | | 3x+9-4x=29 | | -4(-6x-4)-8x=8(2+8x) | | 10z=20 | | 22b^2+b-30=0 | | -26+p=-p+56p+28 | | 1/3(c-9)=-1 |

Equations solver categories